A reconstructed discontinuous Galerkin method for compressible flows in Lagrangian formulation. (30th April 2020) - Wang, Chuanjin; Luo, Hong; Shashkov, Mikhail
Highlights: A reconstructed DG (rDG) method in a new Lagrangian formulation is developed. The Lagrangian formulation is the limit of the unsplit rDG-ALE formulation. A new characteristic limiting procedure is presented. The developed rDG method can attain the designed high order of accuracy. The characteristic limiting strategy outperforms the limiter on physical variables. Abstract: A high-order accurate reconstructed discontinuous Galerkin (rDG) method is developed for solving two-dimensional hydrodynamic problems in cell-centered updated Lagrangian formulation. This method is the Lagrangian limit of the unsplit rDG-ALE formulation, and is obtained by assuming the equality of the grid velocity to the fluid velocity only at cell boundaries. The conservative variables and the Taylor basis defined on the time-dependent moving mesh, provide the piece-wise polynomial expansion in the updated Lagrangian formulation. A multi-directional nodal Riemann solver is implemented for computing the grid velocity at the vertices and the numerical flux at the cell boundaries. A characteristic limiting procedure is extended from the primitive variable version to the conservative variable version, and its performance is compared with the limiter on physical variables. A number of benchmark test cases are conducted to assess the accuracy, robustness, and non-oscillatory property of the DG(P0), DG(P1) and rDG(P1P2) methods. The numerical experiments demonstrate that the developed rDG method is able to attain the designed order of accuracy and the characteristic limiting procedure outperforms the limiter on physical variables in terms of the monotonicity and symmetry preservation for shock problems.